Hernández Guerrero, María José; Marín Hernández, David; Rodríguez Espinosa, Marcos (ed.). Las variedades del español en la traducción editorial y audiovisual: Políticas, tendencias y retos - Susana Schoer Granado (Quaderns)
Hernández Guerrero, María José; Marín Hernández, David; Rodríguez Espinosa, Marcos (ed.) Las variedades del español en la traducción editorial y audiovisual: Políticas, tendencias y retos Granada: Comares, 2024, 468 p. ISBN 978-84-1369-579-2